2017
DOI: 10.3390/ijms19010097
|View full text |Cite
|
Sign up to set email alerts
|

Motor, Somatosensory, Viscerosensory and Metabolic Impairments in a Heterozygous Female Rat Model of Rett Syndrome

Abstract: Rett Syndrome (RTT), an autism-related disorder caused by mutation of the X-linked Methyl CpG-binding Protein 2 (MECP2) gene, is characterized by severe cognitive and intellectual deficits. While cognitive deficits are well-documented in humans and rodent models, impairments of sensory, motor and metabolic functions also occur but remain poorly understood. To better understand non-cognitive deficits in RTT, we studied female rats heterozygous for Mecp2 mutation (Mecp2−/x); unlike commonly used male Mecp2−/y ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
3
12
1
Order By: Relevance
“…Mechanical hypersensitivity is an emerging finding in RTT research. Two recent studies showed marked skin hyperinnervation [59], and mechanical hypersensitivity in one male rat model proposed to study RTT, and somatosensory and viscerosensory alteration in female rats of the same model [59,60]. In striking agreement, another study demonstrated increased sensory fiber innervation in skin biopsies from RTT patients [61].…”
Section: Discussionmentioning
confidence: 63%
“…Mechanical hypersensitivity is an emerging finding in RTT research. Two recent studies showed marked skin hyperinnervation [59], and mechanical hypersensitivity in one male rat model proposed to study RTT, and somatosensory and viscerosensory alteration in female rats of the same model [59,60]. In striking agreement, another study demonstrated increased sensory fiber innervation in skin biopsies from RTT patients [61].…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies report modest deficits in motor function in Mecp2 heterozygous or KO animal models [3,13,24,26,29,31,32], but these deficits largely fail to replicate the substantial motor dysfunction observed in Rett patients. Given the appearance of deficits on a challenging auditory task, we next sought to characterize acquisition and performance of Mecp2 rats on a skilled forelimb motor task.…”
Section: Resultsmentioning
confidence: 95%
“…Rats were generated by breeding a Mecp2 heterozygous Sprague-Dawley female with a wild-type Sprague-Dawley male. Female breeders were obtained from Horizon Discovery (SAGE labs), using zinc finger nuclease technology that generated a 71 base pair deletion in exon 4 [3,9,31]. Experimenters were blind to the genotype.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female Mecp2-deficient rats also recapitulated the motor and behavioral phenotype observed in existing mouse models. More recently, two studies published by the Smith lab showed neuronal cytoskeletal gene dysregulation and mechanical hypersensitivity in the male rat model and non-cognitive deficits (motor, somatosensory, viscerosensory, and metabolic impairments) in the female rat model 43 , 44 . To date, research using these new rat models has confirmed the observations made in the mouse; it will be interesting to see whether future studies will only replicate and validate results obtained in the mouse or bring new findings specific to the rat.…”
Section: Preclinical Models Of Rett Syndromementioning
confidence: 99%